Comparative transcriptomic insights into the domestication of Pleurotus abieticola for coniferous cultivation - Sun, Lei; Sossah, Frederick Leo; Li, Yu; Sun, Huiying (Frontiers in Molecular Biosciences, 2024)
Introduction:Pleurotus abieticola, a promising edible fungus in the Pleurotaceae family, especially its ability to utilize coniferous substrate, holds significant potential for commercial cultivation. However, few reports on the adaptation of P. abieticola to coniferous substrate from the perspective of omics. Methods: This study explores the biological characteristics, domestication process, and nutritional composition of P. abieticola, along with its adaptability to coniferous substrates using transcriptomics. We assessed biological characteristics, optimizing mycelial growth on agar medium with varied carbon and nitrogen sources, temperature, and pH. Additionally, the optimization process extended to fruiting bodies, where impact on the differentiation were evaluated under varying light conditions. Fruiting body nutrient composition was analyzed per the Chinese National Food Safety Standard. Transcriptome sequencing focused on P. abieticola mycelial colonized coniferous and broadleaved substrates. Results and Discussion: The optimal conditions for mycelial growth were identified: dextrin (carbon source), diammonium hydrogen phosphate (nitrogen source), 25°C (temperature), and pH 7.0. White light promoted fruiting body growth and differentiation. Larch substrate exhibited superior yield (190 g) and biological efficiency (38.0%) compared to oak (131 g, 26.2%) and spruce (166 g, 33.2%). P. abieticola showcased high dietary fiber, protein, and total sugar content, low fat, and sufficient microelements. Transcriptome analysis revealed significant key genes involved in lignocellulose degradation, stress-resistant metabolism, and endocytosis metabolism, underscoring their pivotal for coniferous adaptation. This study offers valuable insights for the commercial development and strain breeding of P. abieticola, efficiently leveraging conifer resources. The findings underscore its potential as a valuable source for food, medicinal products, and biotechnological applications.